The Surgical Treatment of Mycetoma. - Suleiman Hussein Suleiman; El Sammani Wadaella; Ahmed Hassan Fahal (Public Library of Science (PLoS), 2016)
Surgical intervention is an integral component in the diagnosis and management of mycetoma. Surgical treatment is indicated for small, localised lesions and massive lesions to reduce the mycetoma load and to enable better response to medical therapy. It is also a life-saving procedure in patients with massive disease and sepsis. Surgical options for mycetoma treatment range from a wide local surgical excision to repetitive debridement excisions to amputation of the affected part. Adequate anaesthesia, a bloodless field, wide local excision with adequate safety margins in a suitable surgical facility, and expert surgeons are mandatory to achieve the best surgical outcome. Surgical intervention in mycetoma is associated with considerable morbidity, deformities, and disabilities, particularly in advanced disease. These complications can be reduced by educating patients to seek medical advice earlier when the lesion is small, localised, and amenable to surgery. There is no evidence for mycetoma hospital cross infection. This communication is based on the authors' experience in managing over 7,200 mycetoma patients treated at the Mycetoma Research Centre, University of Khartoum, Sudan.